A role for microglial cells in reshaping neuronal circuitry of the adult rat auditory brainstem after its sensory deafferentation. Issue 4 (20th January 2014) - Janz, Philipp; Illing, Robert‐Benjamin
<x xml:space="preserve">Abstract</x> Cochlear ablation triggers cellular and molecular reactions in the adult mammalian central auditory system, leading to complex rearrangements in the cellular networks of the auditory brainstem. The role of microglial cells in these processes is largely unknown. We analyzed morphological and molecular responses as well as cellular affiliations of microglia in the auditory brainstem 1 and 7 days after unilateral sensory deafferentation of the cochlear nucleus. In the ventral cochlear nucleus (VCN), morphological changes of microglial cells were evident following cochlear ablation. Microglial activation preceded astroglial hypertrophy in VCN and lateral superior olive (LSO). During axonal degeneration in VCN early after cochlear ablation, p‐ERK1/2‐ and p‐p38‐immunoreactive microglia displayed a hypertrophied phenotype, with processes partially surrounding glutamatergic but not GABAergic synapses. During the peak of VCN reinnervation 1 week after cochlear ablation, the number of microglial cells increased massively. Microglia now displayed dense ramifications juxtaposed to Gap43‐immunoreactive axons and their terminals. Moreover, we identified lesion‐dependent changes in the populations of microglia and astrocytes in LSO and inferior colliculus. By covisualizing cytological markers such as NeuN, GFAP, CD11b, vGluT‐1, GAD‐65, and Gap43 with the prominent MAP kinases ERK1/2 and p38, we show that MAPK signaling is affected by sensory deafferentation in microglia but not in astroglia or in neurons. In conclusion, microglia displaying MAPK signaling appear to contribute to an adaptive response in central auditory regions that was directly or indirectly affected by sensory deafferentation. Moreover, microglial cells are temporally and spatially in place to participate in synaptogenesis inside VCN. © 2014 Wiley Periodicals, Inc.